Tinjauan Yuridis Batasan terhadap Gratifikasi Dan Hadiah Berdasarkan Undang-Undang Nomor 20 Tahun 2001 Tentang Perubahan atas Undang-Undang Nomor 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi - Elsi Renhar; Erdianto '; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of the crimes that are not able to be accommodated by the Laws and Regulations of the State of Indonesia is the Criminal Act of Gratification. New gratification is known in Law Number 20 of 2001 Amendment to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. The essence of this legal normative research is more about the limits of gratification and gifts in Indonesia. So from this, these restrictions use Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning Eradication of Corruption.There are two formulation of the problem in this study, namely, First, how are the limits on gratuities and gifts based on Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning Eradication of Corruption? Second, how ideally should gratification be regulated as a crime in Indonesia?There are 2 conclusions from this study, namely, First, Limitation on gratuities and prizes based on Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning eradication of corruption, there are two, namely a) boundaries from sociological aspects, if seen in terms of social gratification is a natural thing to do, gratification has two characteristics, namely positive and negative and b) the limitations of the juridical aspect, in terms of law which regulates gratuity is divided into two, namely gratification which is considered bribery and gratuities that are not considered bribes. Secondly, Ideally the gratification arrangement as a criminal act in Indonesia is twofold: a) Article 12B and 12C Act Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning eradication of corruption, b) Articles 16 to 18 of Law Law Number 30 of 2002 concerning the Corruption Eradication Commission. There are 2 suggestions in this study, namely: First, Advise law enforcement officers as executors of the Law to propose revisions to Law 20 of 2001 especially related to graft offenses that must be clearly stated as bribery offenses, in addition to standardization of gratuity receipts must also submitted, and also the application of criminal sanctions for State Officials who do not report their assets in LHKPN. Second, the Government immediately establishes its own legislation against acts of gratification, so that there will be no more confusion or misinterpretation of the limitations of acts of gratification as a crime in Indonesia.